Generation of a library of particles having controlled sizes and shapes via the mechanical elongation of master templates - Wang, Yapei (Langmuir : the ACS journal of surfaces and colloids, 2011)
Herein we describe a versatile and readily scalable approach for the fabrication of particles with a variety of shapes and sizes from a single master template by augmenting the particle replication in nonwetting templates (PRINT) method with mechanical elongation. Repetition of the elongation steps in one direction leads to the fabrication of linear particles with high aspect ratio (AR), over 40 times greater than in the original master, while a range of particle shapes can be obtained by repeating the elongation procedure while changing the stretching direction, generating diamond, rectangular, curved parallelogram particles from a single cubic master